Do Solid Pseudopapillary Neoplasms Shrink After Menopause?: Review of the Literature. Issue 6 (August 2015) - Kurokawa, Sachiko; Hirabayashi, Kenichi; Hadano, Atsuko; Yamada, Misuzu; Tajiri, Takuma; Nakamura, Naoya
Abstract : Supplemental digital content is available in the text.